The Effect of Financial Crises on the Relationship between Debt and Economic Growth: Case of the 1997 Asian Financial Crisis - BOULAJRAF , Ilias; RGUIBI , Khalid; HAZZAM , Nour Imane (Revue Internationale du Chercheur, 2023)
This scientific article undertakes an in-depth exploration of the complex impact caused by financial crises on the equally complex dynamics between debt and economic growth. The analysis primarily focuses on the emblematic example of the 1997 Asian Financial Crisis. The study sheds detailed light on how financial crises can act as catalysts, thereby revealing vulnerabilities related to excessive indebtedness and structural imbalances within an economy. When delving into the post-crisis repercussions, it becomes evident that the reforms and actions implemented after this crucial period have played a decisive role in restoring stability and fostering economic recovery. This research underscores the vital importance of enlightened debt management as well as the implementation of robust structural reforms. Such measures aim to mitigate the negative impacts stemming from financial crises and to enhance long-term economic resilience. In summary, this article convincingly demonstrates how financial crises, although disruptive, can also catalyze positive changes and stimulate a thorough reassessment of economic systems.